Local ecological knowledge on seaweed : a case study of the socio-ecological system in Reykhólar, Breiðafjörður - Lee, Jamie, 1985- (2018)
Verkefnið er lokað til 28.10.2019. This thesis is a case study of Reykhólar, a village community which produces products from wild seaweed stock in West Iceland. The purpose is to document and analyze the dynamic interconnections between the society and ecology surrounding rockweed (Ascophyllum nodosum) in order to design sustainable seaweed utilization measures that are applicable to the local social-ecological system. Recent increase in global demand in seaweed products has prompted additional interests to expand the seaweed industry and increase extraction. New marine vegetation policy and management measures are needed to safeguard the health of the ecosystem alongside development. Through conducting interviews, in-field observations and questionnaires with the community and key stakeholders, this study aims to first document the Local Ecological Knowledge (LEK) possessed by the seaweed harvesters and local inhabitants and also to learn from the existing rockweed harvesting management method. A policy comparison with Norway and Canada’s legislations is then used to extract additional legislative recommendations. This research found that there are potentials of overharvesting if harvest licensing decisions were based on an incomplete assessment of the harvestable biomass. Resource degradation or reduced access to the resource will negatively impact the local community. Integrating LEK into adaptive co-management offers important concepts and observations to fill knowledge gaps. This study will inform policy-makers and resource managers about the important considerations for the sustainability of rockweed, ecology and society. Þessi ritgerð er tilviksrannsókn framkvæmd á Reykhólum á Vestfjörðum, þar sem framleiddar eru vörur úr villtum sjávargróðri. Tilgangur rannsóknarinnar er að skjalfesta og greina tengslin á milli samfélags og vistkerfis er varðar klóþang (Ascophyllum nodosum) og mæla með aðgerðum til sjálfbærrar nýtingar sjávargróðurs sem gagnast myndu staðháttum í félags- og visfræðilegu tilliti. ...